DEVELOPMENT OF VIDEO-BASED ARABIC READING LEARNING MEDIA - Siti Nurazizah; Nuruddin Nuruddin; Ihwan Rahman Bahtiar (Thariqah Ilmiah: Jurnal ilmu-ilmu kependidikan & Bahasa Arab, 2023)
This study aims to develop video-based Arabic reading learning media at Al-Azhar Islamic High School Kelapa Gading Jakarta. The research method used is development research with the ADDIE model. The subject of the study was a grade XI student of Al-Azhar Islamic High School Kelapa Gading Jakarta. Development research with the ADDIE model has five stages of research, namely: Analyze, researchers analyze student needs for the development of video-based learning media; Design, researchers collect material and design media to be developed; Development, researchers carry out the process of developing video-based learning media; Implementation, testing products that have been developed; and Evaluation, evaluating activities to determine the quality of media products that have been developed. The results of the material expert assessment get a percentage of 86.67% with the very decent category and the results of the media expert assessment get a percentage of 90.58% with the very decent category and the results of student assessment and evaluation get a percentage of 85.12% with the very decent category.  Based on the assessment above, video-based learning media is suitable to be used as an Arabic learning medium, especially in reading Arabic.